Systematic review of the effect of endodontic irrigants over coronaviruses (Research, Society and Development, 2021)
Objective: This systematic review aimed to discuss a possible effect of sodium hypochlorite (NaOCl) over the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the new generation of corona virus, which was reported firstly in December 2019 in Wuhan, China. Methods: Electronic search was performed for studies up to March 31, 2021 in the following databases: PubMed, LILACS, BBO, Scopus, web of science and Cochrane considering clinical trials and laboratory studies that evaluated the action of NaOCl over SARS-CoV-2. Results: Numerous founded studies reported effectivity of NaOCl in different concentrations and exposure times over corona viruses including the SARS-CoV-2. However, none of the studies evaluated this action in the root canal system. No metanalysis was conducted due to variability of methods or lack of information of included articles. Conclusion: NaOCl has a possible effectivity over SARS-CoV-2 as it dissolves the organic material of virus membrane, but this should be evaluated in the root canal systems.